2015
DOI: 10.1160/th15-01-0062
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphates form antigenic complexes with platelet factor 4 (PF4) and enhance PF4-binding to bacteria

Abstract: Short chain polyphosphates (polyP) are pro-coagulant and pro-inflammatory platelet released inorganic polymers. The platelet chemokine platelet factor 4 (PF4) binds to lipid A on bacteria, inducing an antibody mediated host defense mechanism, which can be misdirected against PF4/heparin complexes leading to the adverse drug reaction heparin-induced thrombocytopenia (HIT). Here, we demonstrate that PF4 complex formation with soluble short chain polyP contributes to host defense mechanisms. Circular dichroism sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 58 publications
3
49
2
Order By: Relevance
“…Mice injected with PF4/nucleic acid complexes develop antibodies that cross-reacted with PF4/ heparin complexes (30). Our microfluidic channel experiments support that PF4 forms complexes with chromatin DNA in the same way as PF4 binds heparin to form macroaggregates (40). Our studies showing that HIT IgG isolated from human plasma binds to these PF4-NET complexes confirm that they contain HIT antigenic epitopes.…”
Section: Discussionsupporting
confidence: 68%
“…Mice injected with PF4/nucleic acid complexes develop antibodies that cross-reacted with PF4/ heparin complexes (30). Our microfluidic channel experiments support that PF4 forms complexes with chromatin DNA in the same way as PF4 binds heparin to form macroaggregates (40). Our studies showing that HIT IgG isolated from human plasma binds to these PF4-NET complexes confirm that they contain HIT antigenic epitopes.…”
Section: Discussionsupporting
confidence: 68%
“…These studies affirm that PF4 can form antigenic complexes with polyphosphates of diverse sizes ranging from those released by platelets to those released by bacteria 20 (Figure 1). The latter suggests a potential new link between the postulated binding of PF4 to bacteria and the genesis of anti-PF4 antibodies responsible for HIT.…”
Section: Discussionsupporting
confidence: 67%
“…One clue toward identifying the pathways that might predispose to delayed thrombotic complications in patients with HIT is the finding that PF4 forms antigenic complexes with a variety of polyanions, including glycosaminoglycans, sulfated anticoagulants, lipid A from gram-negative bacteria, RNA, and inorganic polyphosphates (polyPs). 2,4,[18][19][20][21][22] PolyPs are highly anionic linear polymers of orthophosphate linked by phosphoanhydride bonds. [23][24][25] Although found in all mammalian cells, polyPs are present in the dense granules of human platelets at millimolar concentrations and are released following activation.…”
Section: Introductionmentioning
confidence: 99%
“…LPS reaches a length of up to 25 nm, therefore sterically hiding the Fc part of the IgG for the platelet Fc receptor, as the complex of PF4/lipid A with a bound anti‐PF4/P IgG cannot reach out of the LPS cover. However, we have also shown that polyphosphates can overcome the inhibitory effect of longer LPS chains by forming larger PF4/polyphosphate complexes .…”
Section: Discussionmentioning
confidence: 76%